Meat consumption, stratified by dietary quality, and risk of heart disease. Issue 12 (28th December 2021) - Møller, Sanne Pagh; Mejborn, Heddie; Christensen, Anne Illemann; Biltoft-Jensen, Anja; Thygesen, Lau Caspar
Abstract: Associations between meat consumption and heart disease have been assessed in several studies, but it has been suggested that other dietary factors influence these associations. The aim of the present study was to assess whether meat consumption is associated with ischaemic heart disease (IHD), and if the association is modified by dietary quality. The analyses were based on the cohort of adult participants in the Danish National Survey on Diet and Physical Activity in 2000–2002, 2003–2008 and 2011–2013. From these surveys, information on meat consumption and dietary quality was extracted. The cohort was followed in national registers to identify incident IHD. Associations were estimated using Cox regression analyses adjusting for socio-demographic and lifestyle factors. Analyses of associations between meat consumption and IHD stratified by dietary quality were subsequently evaluated. Among the 8007 participants, the median follow-up was 9·8 years and 439 cases of IHD were recorded. The results suggested a trend between consumption increments of 100 g/d of red meat (hazard ratio (HR) = 1·23; 95 % CI 0·99, 1·53) or of 50 g/d of processed meat (HR = 1·09; 95 % CI 0·93, 1·29) and higher risk of IHD. The trends were, however, not statistically significant. Stratification by dietary quality did not suggest that associations between meat consumption and risk of IHD were modified by dietary quality. This population-based cohort study with detailed dietary information suggested a trend with higher meat consumption being associated with higher risk of IHD, but the association was not statistically significant. Results did not indicate that dietary quality modifies such associations.